Answer:
We kindly invite you to see the explanation for further details.
Step-by-step explanation:
Let [tex]y = \frac{2}{3}\cdot x -3[/tex], where [tex]x[/tex] and [tex]y[/tex] are the independent and dependent variables. From Geometry, we understand that all line can be formed by knowing two distinct points. We select [tex]x_{1} = 0[/tex] and [tex]x_{2} = 3[/tex] and we obtain the respective dependent values:
x = 0
[tex]y = \frac{2}{3}\cdot (0) -3[/tex]
[tex]y_{1} = -3[/tex]
x = 3
[tex]y = \frac{2}{3}\cdot (3)-3[/tex]
[tex]y_{2} = -1[/tex]
Lastly, we plot the resulting line with the help of a graphing tool.